The influence of exogenous elements on technological innovation system development: the case of rainwater harvesting for irrigation in Kenya - Singh, R.; Minh, Thai Thi; Oguge, N.; Odote, C. (Innovative Space of Scientific Research Journals, 2023)
Rainwater harvesting for irrigation can increase sustainable access to irrigation and improve farmer resilience to climate change, particularly in semi-arid regions of sub-Saharan Africa. However, attempts to increase adoption of rainwater harvesting for irrigation in Kenya have rarely been successful, despite decades of efforts by governments, NGOs, and development practitioners. Most scholars investigating reasons for these low levels of adoption tend to focus on hydrogeological, techno-managerial, or socio-economic factors, and leave out explanations grounded in the analysis of macro-level cultural, political, economic, and environmental dynamics within a specific context. To fill this gap, this article analyzes historical processes of two sites to identify how these dynamics contributed to an enabling environment for rainwater harvesting for irrigation in Kenya. The concept of technological innovation systems, which describes processes central to the emergence, growth, and diffusion of technological innovations, was used as a lens to examine long-term rainwater harvesting for irrigation adoption dynamics in the two sites. The identification of elements «exogenous» to the innovation system demonstrated that ecological, demographic, macroeconomic, political, cultural, and socio-economic elements exerted a major influence on the development of an enabling environment for rainwater harvesting for irrigation. Exogenous elements influenced levels of adoption by shaping the capacity and quality of elements within rainwater harvesting innovation systems, giving rise to systemic problems or opportunities, and influencing the speed of system development.